Estudio de mercadeo para la introducción y posicionamiento de comprimidos masticables de Jengibre y Propóleo en la ciudad de Quito - Muñoz Beltrán, Leopoldo Fernando (2012)
Based on studies by the World Health Organization, 80% of Ecuador's population depends on alternative medicine and therefore ancestral plants and natural products to cure their illnesses and ailments. And they are in the cities of the Ecuadorian highlands where the influence of the cold weather affects people with respiratory disease, offering the opportunity to introduce a natural product based on compressed Jengibre & Propóleo, allowing combat flu symptoms in population. Therefore, the objective of this study is the introduction and positioning of these products successfully in the market of the city of Quito, in 2012.